2011
DOI: 10.1158/0008-5472.can-10-3445
|View full text |Cite|
|
Sign up to set email alerts
|

ΔNp63 Versatilely Regulates a BroadNF-κBGene Program and Promotes Squamous Epithelial Proliferation, Migration, and Inflammation

Abstract: Head and neck squamous cell carcinoma (HNSCC) and many epithelial malignancies exhibit increased proliferation, invasion and inflammation, concomitant with aberrant nuclear activation of TP53 and NF-κB family members ΔNp63, c-REL and RELA. However, the mechanisms of crosstalk by which these transcription factors coordinate gene expression and the malignant phenotype remain elusive. Here we demonstrate thatΔNp63 regulates a cohort of genes involved in cell growth, survival, adhesion and inflammation, which subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
134
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(155 citation statements)
references
References 46 publications
20
134
1
Order By: Relevance
“…Indeed, loss of function of ΔNp63 enhances terminal maturation in stratified squamous epithelium (41). On one hand, ΔNp63α overexpression has been shown in a rat cell line to accelerate tumor growth in nude mice (42), and transgenic mice overexpressing ΔNp63α develop epidermal hyperplasia (43). Tp63 was recently shown to be required for maintenance of tumors, as inducible genetic deletion of all its isoforms led to blockade of chemically induced SCC formation in mice (44).…”
Section: Figurementioning
confidence: 99%
“…Indeed, loss of function of ΔNp63 enhances terminal maturation in stratified squamous epithelium (41). On one hand, ΔNp63α overexpression has been shown in a rat cell line to accelerate tumor growth in nude mice (42), and transgenic mice overexpressing ΔNp63α develop epidermal hyperplasia (43). Tp63 was recently shown to be required for maintenance of tumors, as inducible genetic deletion of all its isoforms led to blockade of chemically induced SCC formation in mice (44).…”
Section: Figurementioning
confidence: 99%
“…Epithelial differentiation: Keratin 1 (KRT1) -KRT1 is a marker for terminal differentiation in the mammalian epidermis (Lessin et al, 1988;Huang et al, 2012). Through protein-protein interactions with other transcription and cofactors, TP63 also contributes to the transcriptional regulation of genes involved in cellular differentiation, proliferation/survival, growth suppression, apoptosis, adhesion, inflammation, and metabolism (Perez and Pietenpol, 2007;Viganò and Mantovani, 2007;Yang et al, 2011). Recent work by our laboratory has identified protein-protein interactions between ∆Np63α, TAp73, and c-REL that function to regulate key genes involved in growth arrest and apoptosis of mutant p53 head and neck squamous cell carcinoma (HNSCC) .…”
Section: Functionmentioning
confidence: 99%
“…Apoptosis: p53-Upregulated Modulator of Apoptosis (PUMA) -PUMA binds to BCL2 to induce rapid and profound apoptosis by cytochrome c release (Yu et al, 2001;Flores et al, 2002). Additionally, recent work has shown that a complex of ∆Np63α, with TAp73 or c-REL, can modify expression of key growth arrest and apoptotic genes such as p21WAF1, NOXA, and PUMA Yang et al, 2011). Adhesion: Integrin Alpha 6 (ITGA6) -ITGA6 is a cell surface adhesion molecule that may help regulate migration and layer formation, especially in epithelial cells.…”
Section: Functionmentioning
confidence: 99%
See 2 more Smart Citations